Paediatric elbow fractures and public play spaces: adherence to standards for children's playground equipment and surfacing - Harpreet Chhina; Anthony Cooper; Jennifer Smith; Ian Pike; Mariana Brussoni; Pardeep Sidhu (BMJ Publishing Group, 2021)
Background Supracondylar humerus fractures (SCHF) are the most common fractures sustained following a fall onto an outstretched hand among healthy children, and one of the leading causes of hospital admission and surgical intervention. The aim of this study was to examine SCHF occurring at public play spaces-particularly to determine whether or not the playground equipment implicated in injurious falls aligned with Canadian playground safety standards.Methods Cases of children who attended the provincial paediatric orthopaedic clinic following SCHF at a public playground between April 2017 and October 2019 were included in the study. A research assistant visited each playground to measure the play structure type and dimensions, height of the equipment at the point from which the child fell and the type and depth of the surface material, and compare measurements to the 2016 safety standards. Child demographics and injury classification were also noted. Descriptive statistics were calculated and a scatterplot of fall height and surface depth was generated.Results Forty-three sites, representing 47 SCHF cases (18 female, 29 male), were included in the final analysis. Fourteen children sustained type 1 fracture, 23 had type 2 fracture and the remaining 10 had type 3 fracture. Five children with type 2 fracture and all 10 children with type 3 fracture required surgery. The majority of sites had engineered wood fibre surfacing, with surfacing at 35 sites being less than 300 mm deep. Twenty-six play structures were upper body equipment (ie, monkey bars or similar), seven were track rides, five were rotating structures and the rest comprised a variety of classified and unclassified structures. Twenty-seven children fell from a height exceeding 2 m.Conclusions The majority of SCHF cases occurred at playgrounds with insufficient surface depth and/or non-compliant equipment. Upper body equipment, track rides and rotating play structures were of particular concern, as the children fell from heights exceeding the recommended standard, likely reflecting the degradation and compaction of the surfacing material over time.